Incidence of Thrombocytopenia in Pregnant Females - Saba, Nasim; Rashid, Sobia; Ayub, Hina (Indus Journal of Bioscience Research, 2025)
Introduction: Thrombocytopenia or low platelet counts are frequent hematologic findings in pregnancy, possibly affecting both the mother and her fetus. This paper aims to establish its prevalence and determinants among pregnant females in the Department of Gynaecology and Obstetrics, District Headquarter Teaching Hospital/ Gomal Medical College, Dera Ismail Khan, Pakistan. Objectives: To assess the frequency, causes, and outcome of thrombocytopenia in pregnant females in a tertiary Health Care teaching Institute. Materials and Methods: The cross-sectional observational study was conducted at Department of Gynaecology and Obstetrics, District Headquarter Teaching Hospital/ Gomal Medical College, Dera Ismail Khan, Pakistan in the duration from June, 2024 to November, 2024. Subjects: this regimen is for pregnant females between 18 and 45 years of age with thrombocytopenia that was documented to be